Phonotactic and phrasal properties of speech rhythm. Evidence from Catalan, English, and Spanish - Prieto, P; Vanrell, MDM; Astruc, L; Payne, E; Post, B (Elsevier, 2011)
The goal of this study is twofold: first, to examine in greater depth the claimed contribution of differences in syllable structure to measures of speech rhythm for three languages that are reported to belong to different rhythmic classes, namely, English, Spanish, and Catalan; and second, to investigate differences in the durational marking of prosodic heads and final edges of prosodic constituents between the three languages and test whether this distinction correlates in any way with the rhythmic distinctions. Data from a total of 24 speakers reading 720 utterances from these three languages show that differences in the rhythm metrics emerge even when syllable structure is controlled for in the experimental materials, at least between English on the one hand and Spanish/Catalan on the other, suggesting that important differences in durational patterns exist between these languages that cannot simply be attributed to differences in phonotactic properties. In particular, the vocalic variability measures nPVI-V, ΔV, and VarcoV are shown to be robust tools for discrimination above and beyond such phonotactic properties. Further analyses of the data indicate that the rhythmic class distinctions under consideration finely correlate with differences in the way these languages instantiate two prosodic timing processes, namely, the durational marking of prosodic heads, and pre-final lengthening at prosodic boundaries.